Effects of accelerated aging on characteristics, leaching, and toxicity of commercial lead chromate pigmented microplastics - Luo, Hongwei; Li, Yu; Zhao, Yaoyao; Xiang, Yahui; He, Dongqin; Pan, Xiangliang (Environmental pollution (1987), 2020)
It is of environmental significance to study the leaching performance of additives from microplastics (MPs) and further evaluate the toxicity of leachate to microalgae. Here, we investigated the effects of accelerated aging on characteristics, leaching, and toxicity of commercial lead chromate pigmented MPs. Results show that aging of MPs caused surface cracks and fragmentation, increased their surface area and carbonyl contents, and promoted the release of lead chromate pigment. Chromium (Cr) and lead (Pb) tend to leach under acidic condition, rather than neutral and alkali environment. Aging treatment facilitates the leaching performance and a high concentration of NaCl solution also favors the leaching process. Toxicology experiments demonstrate that only high concentration of leachate (>10 μg L−1) exerted significant inhibitory influence (p < 0.005) on cell photosynthesis of Microcystis aeruginosa. The growth inhibition of algal cells remarkably increased with increasing leachate concentrations. We observed more inhibiting effects on cell growth and photosynthesis using the leachates of aged MPs. Longer aging time leads to more release of Cr and Pb, rendering higher toxicity to microalgae. These novel findings will benefit us from assessing the leaching behavior of additives in MPs and their toxicological risks to aquatic organisms. [Display omitted] •Aging of microplastics promoted the release of pigments.•Growth inhibition of algal cells increased with increasing leachate concentrations.•More inhibiting effects on cell growth and photosynthesis under aging conditions were observed.•Longer aging time led to more release of Cr and Pb, rendering higher toxicity to microalgae. Accelerated aging promotes the release of pigments from MPs and increases the toxicity of leachate to Microcystis aeruginosa.